Predictors of physical activity in school attending adolescents in Lagos State, Nigeria - Adebusoye, Busola (2023)
Background Physical activity has been shown to be a significant protective factor for different health outcomes. The World Health Organization (WHO) recommends that children and adolescents should accumulate at least 60 minutes of moderate-to-vigorous-intensity physical activity (MVPA) daily. Africa is rapidly undergoing an unprecedented phase of urbanisation and how to ensure healthy lives for its residents is increasingly becoming an important question. Some of the immediate effects of urbanisation are pressures on existing built environment. Previous reviews have synthesised associations between the built environments and physical activity in children and adolescents, but they have focused on non-African settings. Therefore, the first objective of this PhD study was to present evidence on the built environment constructs that were associated with physical activity among children and adolescents in Africa. Lagos occupies a unique position in West Africa subregion, as the city with the highest rate of urbanisation. As with most cities that are going through urbanisation, inequitable distribution of resources in different areas of the city affect physical activity. The second objective was to determine the proportion of school attending adolescents that reached the recommended MVPA level in Lagos State, Nigeria and to identify the predictors that were associated with reaching the recommended level. And finally, the third objective was to explore the barriers and facilitators of physical activity among school attending adolescents in Lagos State, Nigeria.